PENGARUH PERTUMBUHAN PENJUALAN DAN PERPUTARAN PERSEDIAAN TERHADAP PERTUMBUHAN LABA: Studi Kasus PT. Hero Supermarket, Tbk. - Sadik Sadik; Samsul Anwar; Ita Friyanti (Universitas Wiralodra, 2025)
A This study aims to examine the effect of Sales Growth and Inventory Turnover on Profit Growth at PT Hero Supermarket Tbk. during the period 20192024. Employing a quantitative approach with an associative method, the research utilizes secondary data in the form of annual financial statements retrieved from the Indonesia Stock Exchange. Data analysis techniques employed include multiple linear regression, t-test, F-test, correlation analysis, and the coefficient of determination, with the assistance of SPSS version 25.The results reveal that neither Sales Growth nor Inventory Turnover exerts a statistically significant influence on profit growth, both individually and jointly. Sales Growth exhibits a very weak positive correlation with profit growth, while Inventory Turnover displays a moderate negative correlation, yet both are statistically insignificant. These findings suggest that other internal or external factors may serve as more substantial determinants of profit growth in the context of the observed firm.